Avoiding pitfalls in ankle fracture-dislocations: A case report of a dislocated tibialis posterior tendon causing persistent ankle subluxation. Issue 6 (August 2021) - Tschudi, Samuel; Wittauer, Matthias; Hirschmann, Anna; Eckardt, Henrik
Highlights: Tibialis posterior tendon dislocation in ankle fracture-dislocations can impede anatomical reduction of the ankle mortise. Need for performance of CT or MRI if reduction is insufficient and the cause cannot be found intraoperatively. Importance of careful evaluation of soft-tissue structures on CT-scans for tendon pathologies and interposition. In CT/MRI additional soft tissue between talus and medial malleolus is an important sign of TPT interposition. Understanding the trauma mechanism and the course of the dislocated tendon enables surgeons to early diagnose this condition. Abstract: Tibialis posterior tendon dislocation, a rare complication in ankle fracture-dislocations, can impede anatomical reduction of the ankle mortise. We report on a 59-year-old healthy male with an open fracture-dislocation of the right ankle. Despite multiple attempts under direct vision of the anterior syndesmosis, anatomical reduction of the ankle mortise was not possible. Soft tissue windows in a computed tomography (CT) scan revealed the dislocated tibialis posterior tendon to be the impeding structure. At the level of the fibula fracture the tendon passed through the interosseous membrane anterior to the distal tibia and was then incarcerated in the medial talocrural joint before returning to the flexor retinaculum and its insertion on the navicular bone. Understanding the trauma mechanism and the course of the dislocated tendon as well as correct interpretation of CT and magnetic resonance images of the ankle enable surgeons to early diagnose and correctly treat this condition.